GERAKAN REMAJA SADAR LITERASI DAN PEDULI KESEHATAN “GRADASI PELITA” SEBAGAI BENTUK PEMBERDAYAAN REMAJA DALAM UPAYA PENCEGAHAN COVID 19 - Nina Dwi Lestari; Yanuar Fahrizal (LPPM IST AKPRIND Yogyakarta, 2021)
The number of Covid-19 sufferers in Indonesia, especially in Yogyakarta, has increasedevery day. The potential for the spread of Covid-19 can not be separated from misconceptionregarding Covid-19. Teenagers are one of the aggregates that can increase generalunderstanding of the importance of preventing Covid-19 by pioneering clean and healthyliving habits (PHBS) in the community. This service activity aims to increase publicawareness of the importance of clean and healthy living habits in preventing the transmissionof Covid-19 by empowering youth in the Rt 24, Rw 12, Kaliagung, Sentolo, Kulon Progo, DIYareas in health promotion. The method used is the formation and training of youth cadres, thedoor-to-door rise of PHBS, mass disinfection in people's homes and public facilities, andadvocacy to community leaders in the formation of calls for implementing PHBS. Results: Theappearance of 8 youth health cadres, increased community awareness about PHBS asevidenced by the ability to use masks properly and wash hands with six steps 60% correct,increased knowledge of residents related to Covid-19 in good categories (28.9%),implementation of disinfection in 40 residents' houses and public facilities such as mosques,guard posts and crowd centers. A regulation was formed to increase the implementation ofPHBS in the community